2002
DOI: 10.1097/00004872-200212000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Pulse wave velocity and the second derivative of the finger photoplethysmogram in treated hypertensive patients

Abstract: The results suggest that in hypertensive patients, PWV and SDPTG provide different information about arterial properties at central and peripheral sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 21 publications
6
74
0
4
Order By: Relevance
“…Attempts at providing a less intrusive methodology have resulted in determination of parameters related to PTT from recording of a single pulse trace, such as the use of the second derivative of the finger photoplethysmogram. 14 Although of limited use, this method has not shown a strong association with PWV. 14,15 In this present study, we propose a novel noninvasive and less intrusive method to assess arterial stiffness from a single peripheral pulse waveform.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Attempts at providing a less intrusive methodology have resulted in determination of parameters related to PTT from recording of a single pulse trace, such as the use of the second derivative of the finger photoplethysmogram. 14 Although of limited use, this method has not shown a strong association with PWV. 14,15 In this present study, we propose a novel noninvasive and less intrusive method to assess arterial stiffness from a single peripheral pulse waveform.…”
mentioning
confidence: 98%
“…14 Although of limited use, this method has not shown a strong association with PWV. 14,15 In this present study, we propose a novel noninvasive and less intrusive method to assess arterial stiffness from a single peripheral pulse waveform. This method determines carotidto-femoral PTT from the radial pressure waveform, which is transformed to derive the central aortic pressure waveform via a validated transfer function.…”
mentioning
confidence: 98%
“…Study by Woodman et al (2003) found that SI DVP correlated to PWV (r=0.54). Hashimoto et al (2002) observed that among hypertensive subjects, PWV correlated to B/A (b/a) ratio obtained by analyzing the second derivative PPG, which is a proposed index of AS. However, this correlation became insignificant after adjustment for the age and MAP (r=0.16).…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13] One transducer was positioned over the left common carotid artery and another was placed over the left femoral artery. The device simultaneously recorded the ECG and phonocardiogram (PCG).…”
Section: Pwv Measurementmentioning
confidence: 99%